(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The “ONLINE AUCTION SYSTEM” is a web-based platform designed to facilitate the buying and selling of a wide range of products and services through an efficient and transparent auction mechanism. This system aims to provide a user-friendly and secure environment for both sellers and buyers, enabling them to participate in auctions, set bid prices, and monitor auction progress in real-time. Key features of the system include user registration, item listing, bid management, and secure payment processing. By leveraging modern technology, the Online Auction System streamlines the auction process, enhances users experience, and ensures fair competition, making it a valuable tool for individuals and businesses engaged in online trading and auctions.